(untitled) (Journal of Dhaka National Medical College & Hospital, 2021)
Background: The upper limb is unique both structurally and functionally. It is the most movable part and main working tools of human body which is used for maintaining balance, carrying, touching, cognition, holding, gripping and for performing various fine works. Objectives: To determine the upper limb dimensions of the adult Bangladeshi women. Methods: This descriptive and analytical study was carried out in the department of Anatomy, Sir Salimullah Medical College, Dhaka from July 2010 to December 2011. The ethical permission was taken from Institutional Ethics Committee (IEC) of SSMC. Total 100 adult Bangladeshi women of 25 to 45 years were studied. Length of radius & ulna were measured directly from the subjects by using anthropometric spreading caliper. Statistical analysis was done by two sample z-test & pearson correlation coefficient test. Result: The length of both right & left radius and also both right & left ulna showed significant positive correlation with stature. Conclusion: This study provides the direction to construct baseline data of upper limb anthropometry of adult Bangladeshi women. J. Dhaka National Med. Coll. Hos. 2021; 27 (01): 12-16